Plastic Solid Waste Management Assessment Among Selected Schools in Gwadabawa Local Government, Sokoto, Nigeria - Gada, Sahabi Nasibatu (Darul Yasin Al Sys, 2024)
The objective of this work was to assess the plastic solid waste management among selected schools in Gwadabawa Local Government, Sokoto, Nigeria. A descriptive survey (cross-sectional) study was employed and collected data from portions of schools and respondents. The findings indicate that, demographic characteristics of teacher respondents involved in this study are: Males are 66.7%, females are 33.3%; and the levels of education include, NCE/diploma (58.0%), BSc (26.7%), MSc (13.3%), and PhD (2.0%). Regards to students involved, 48.0% are males, 60.0% are females; 36.0% are 18-20 years old, and 64.0% are above 20 years old. The level of education of students include, 60.0% diploma students, and 40.0% certificates students. The effects are listed in the order of frequency as submitted by participants: Release of gases (20.5%), land pollution (17.0%), water pollution (15.0%), attraction of vermin (11.0%), breeding of diseases (10.5%), loss of biodiversity (7.5%), reduction of beauty of environment (7.5%), offensive odour (5.0%), flooding (5.0%), and particulates release (1.0%). Methods of waste elimination are: open disposal occurs among 37.5% schools; likewise, open disposal and burning, occur in 37.5%; while, use as fertilizer was recorded in 12.5% schools. Waste collection methods are either open dumping (80.0%), or use of containers (20.0%). The use of segregation of waste; therewith, only 20.0% practice segregation, the remaining 80.0% do not practice segregation, rather openly display mixtures of waste materials. The possible remedies to mitigate plastic solid waste mismanagement and effects include, education (awareness) and behavior change (53.3%) was mostly stated, funding (26.7%), improvisation (15.3%), scavenging (3.3%), and innovations (1.3%). Policy makers need to act urgently in diverse ways, and the people are supposed to be educated on ways of remediating plastic waste pollution.